Development models and policies for higher education: a theoretical approach (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
Development models historically have impacted higher education in Latin America giving it particular characteristics. The purpose of this research is to examine the role of the state through the analysis of policies for university education in the context of development models. the assumption that q is handled is developing models that the state takes, ironically hampered the need for transformation at all levels of education and the university does not escape this reality. Preliminary results realize the following: Development models the state that have been affected directly drives the conformation of public policies for education at all levels; subjects with power of decision in the conformation process of public policies for education in the state apparatus have privileged background interests which respond to these development models; and last, but in the decade, some Latin American countries are pushing a counter-hegemonic development model, it has not established a new development model that moves away from the interests of capital.
Keywords: development models; public policy; higher education; transformation